2021
DOI: 10.1001/jamanetworkopen.2021.36798
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Pocket Costs for Colonoscopy After Noninvasive Colorectal Cancer Screening Among US Adults With Commercial and Medicare Insurance

Abstract: This economic evaluation examines whether adult patients in the US who have commercial or Medicare insurance pay out-of-pocket costs associated with follow-up colonoscopy within 6 months of a noninvasive stool-based test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…However, cost barriers remain for some individuals with a positive test that requires a follow-up colonoscopy. 1 In response, state-level policies have been enacted in Kentucky (2016), Oregon (2017), and California (2021) to eliminate financial disincentives that may deter follow-up colonoscopy for these individuals. In January 2022, federal guidance was issued to remove cost-sharing for colonoscopies following noninvasive CRC screening tests for commercial insurers, and a similar policy is under consideration for Medicare.…”
Section: Introductionmentioning
confidence: 99%
“…However, cost barriers remain for some individuals with a positive test that requires a follow-up colonoscopy. 1 In response, state-level policies have been enacted in Kentucky (2016), Oregon (2017), and California (2021) to eliminate financial disincentives that may deter follow-up colonoscopy for these individuals. In January 2022, federal guidance was issued to remove cost-sharing for colonoscopies following noninvasive CRC screening tests for commercial insurers, and a similar policy is under consideration for Medicare.…”
Section: Introductionmentioning
confidence: 99%
“…Colonoscopy is an essential tool in the effort to reduce CRC burden. Unfortunately, many Americans face cost-sharing for a clinically indicated colonoscopy following a positive stool-based test, which may deter use of this potentially life-saving intervention ( Fendrick et al, 2021b ). The estimated LYG/colonoscopy was approximately 3-fold higher for procedures performed in follow-up of a positive stool-based screening test when compared with screening colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…However, cost barriers remain for some individuals with an initial positive stool-based test that requires a follow-up colonoscopy to complete the CRC screening process. Coverage policies that impose this type of financial disincentive may deter CRC screening participation ( Fendrick et al, 2021b ). The objective of this analysis was to estimate and compare the life-years gained (LYG) per average-risk screening colonoscopy and follow-up colonoscopy after a positive stool-based test to better inform CRC coverage policy and reimbursement decisions.…”
Section: Introductionmentioning
confidence: 99%
“…18 Nevertheless, there is evidence that consumer cost sharing remains common. Fendrick et al 19 recently found that cost sharing for CRC screening occurred in 48.2% of patients with commercial insurance and 77.9% of patients with Medicare coverage.…”
Section: Evidencementioning
confidence: 99%